Lean principles and techniques for improving the quality and productivity of software development projects: a case study. (23rd April 2007) - Middleton, Peter; Taylor, Philip S.; Flaxel, Amy; Cookson, Ammon
Software product development is recognised as difficult due to the intangible nature of the product, requirements elicitation, effective progress measurement, and so forth. In this paper, we describe some of the challenges of software product development and how the challenges are being met by lean management principles and techniques. Specifically, we examine lean principles and techniques that were devised by Toyota and other manufacturers over the last 50 years. Applying lean principles to software development projects has been advocated for over ten years and it will be shown that the extensive lean literature is a valuable source of ideas for software development. A case study with a software development organisation, Timberline Inc., will demonstrate that lean principles and techniques can be successfully applied to software product development.